2014
DOI: 10.1016/j.neurobiolaging.2014.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network as a potential biomarker of chemotherapy-related brain injury

Abstract: Chronic medical conditions and/or their treatments may interact with aging to alter or even accelerate brain senescence. Adult onset cancer, for example, is a disease associated with advanced aging and emerging evidence suggests a profile of subtle but diffuse brain injury following cancer chemotherapy. Breast cancer is currently the primary model for studying these “chemobrain” effects. Given the widespread changes to brain structure and function as well as the common impairment of integrated cognitive skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 130 publications
(173 reference statements)
7
70
0
1
Order By: Relevance
“…Functional MRI studies established that DMN is more vulnerable to disease and effects of Table 1. Mean values of the volumes of different brain parts before and 6 months after chemotherapy calculated using coronal MRI chemotherapy in breast cancer patients [13]. Our study also revealed hippocampal volume loss on MRI 6 months after cancer treatment.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Functional MRI studies established that DMN is more vulnerable to disease and effects of Table 1. Mean values of the volumes of different brain parts before and 6 months after chemotherapy calculated using coronal MRI chemotherapy in breast cancer patients [13]. Our study also revealed hippocampal volume loss on MRI 6 months after cancer treatment.…”
Section: Discussionsupporting
confidence: 54%
“…It stores memories and it is also able to recall them [8].In cancer patients several studies reported various cognitive impairments called chemobrain [4,[9][10][11]. Chemobrain was mostly studied and proved in patients who received treatment for breast cancer [6,[11][12][13][14]. In a study with 39 breast cancer patients a decline in concentration and memory in 28% of patients was shown [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairments following breast cancer and its treatments may worsen over time (Wefel, et al, 2010) indicating a persistent or even progressive phenotype. Therefore, cancer and/or its therapies have been theorized to possibly alter or accelerate age-related neurodegeneration (Ahles, 2012; Kesler, 2014; Koppelmans, et al, 2013; Mandelblatt, et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Highly central, “hub” regions participate in a large number of functional interactions and therefore have high metabolic demands (Lord, et al, 2013). These high energy requirements make these regions more vulnerable to age-related reduction of physiologic resources as well as a variety of neuropathologic processes (Crossley, et al, 2014; Kesler, 2014). We have previously demonstrated that hub regions are vulnerable to breast cancer and its treatments (Hosseini and Kesler, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Default mode network includes precuneus, cingulate, medial frontal, middle temporal, and lateral parietal regions as well as the hippocampus and is believed to support implicit learning, monitoring, and allocation of neural resources to various cognitive processes. 22,24,25 The default mode network is an intrinsic functional brain network, meaning that its constituent regions are spontaneously coactive, independent of external stimuli. Such spontaneous, intrinsic connectivity is measured during an extended, task-free “resting” state using fMRI.…”
mentioning
confidence: 99%